The role of pioneering transcription factors, chromatin accessibility and epigenetic reprogramming in oncogenic viruses - Kgatle, Mankgopo; Mbambara, Saidon; Khoza, Leon; Fadebi, Olalekan; Mashamba-Thompson, Tivani; Sathekge, Mike (Frontiers in Microbiology, 2025)
Oncogenic viruses typically manipulate host cellular mechanisms to drive tumorigenesis. They exploit pioneering transcription factors to modify gene expression, enabling uncontrolled proliferation. These viruses alter chromatin accessibility and induce chromatin remodelling, disrupting DNA repair and promoting viral genome integration. Additionally, epigenetic reprogramming through mechanisms like DNA methylation and histone modifications silences tumor suppressor genes and activates oncogenes. Understanding these mechanisms is critical for identifying more improved therapeutic targets, improving diagnostics, and predicting disease progression. Advances in this field can guide the development of innovative treatments and early detection tools. This comprehensive review synthesizes existing knowledge on the contributions of oncogenic viruses such as hepatitis B virus (HBV), hepatitis C virus (HCV), human papillomavirus (HPV), and human T-cell leukaemia virus type 1 (HTLV-1), Epstein–Barr virus (EBV), human herpesvirus 8 (HHV-8), and Merkel cell polyomavirus (MCV) to cancer development, highlighting their therapeutic relevance and driving forward research in viral oncogenesis.